1989
DOI: 10.1210/endo-124-5-2648
|View full text |Cite
|
Sign up to set email alerts
|

Chromosomal Localization of the Human Osteocalcin Gene

Abstract: The human osteocalcin gene was assigned to chromosome 1 by Southern blot analysis of DNAs from a panel of mouse-human somatic cell hybrids with limited numbers of human chromosomes and the complete complement of murine chromosomes. By Southern blot analysis of DNAs from mouse-human hybrids that retain specific segments of human chromosome 1, we have determined that the locus of the human osteocalcin gene is on the long arm of chromosome 1, distal (telomeric) to the -spectrin gene. Osteocalcin is a bone specifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
27
1
1

Year Published

1996
1996
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 71 publications
(30 citation statements)
references
References 0 publications
1
27
1
1
Order By: Relevance
“…Genomic analysis of the osteocalcin gene by restriction enzymes revealed single fragments of similar size in all cell lines studied, confirming that the human osteocalcin gene is a singlecopy gene [Puchacz et al, 1989] and that the local surroundings of the osteocalcin gene are identical in this respect in the cell lines studied. Interestingly, Rahman et al [1993] have identified multiple copies of the osteocalcin gene in rat and mouse strains.…”
Section: Discussionsupporting
confidence: 62%
See 2 more Smart Citations
“…Genomic analysis of the osteocalcin gene by restriction enzymes revealed single fragments of similar size in all cell lines studied, confirming that the human osteocalcin gene is a singlecopy gene [Puchacz et al, 1989] and that the local surroundings of the osteocalcin gene are identical in this respect in the cell lines studied. Interestingly, Rahman et al [1993] have identified multiple copies of the osteocalcin gene in rat and mouse strains.…”
Section: Discussionsupporting
confidence: 62%
“…Further, DNA from MG-63 cells was digested with nine randomly chosen restriction enzymes (Fig. 2B) to confirm that there exists only one copy of the osteocalcin gene in the human genome [Puchacz et al, 1989].…”
Section: Genomic Analysis Of the Osteocalcin Genementioning
confidence: 99%
See 1 more Smart Citation
“…Studies in premenopausal white women and Mexican American adults also confirmed the linkage with BMD [9,10]. The human osteocalcin gene, which is located on chromosome 1 at 1q25-31 lies near 1q21-23 [11]. Studies in mice have confirmed that osteocalcin-deficient mice developed a phenotype marked by higher bone mass [12].…”
Section: Introductionmentioning
confidence: 93%
“…The human osteocalcin gene has been mapped to chromosomal region 1q25-1q31 by somatic cell hybridization (Puchacz et al, 1989). The gene spans approximately 2 kb and includes a TATA box, four exons, and a promoter with binding sites for numerous transcriptional regulators (Celeste et al, 1986;Morrison et al, 1989;Bidwell et al, 1993;Morrison and Eisman, 1993).…”
Section: Introductionmentioning
confidence: 99%